Astragaloside IV, as a potential anticancer agent - Xia, Dongqin; Li, Wenjie; Tang, Ce; Jiang, Juan (Frontiers in Pharmacology, 2023)
Cancer is a global intractable disease, and its morbidity and mortality are increasing year by year in developing countries. Surgery and chemotherapy are often used to treat cancer, but they result in unsatisfactory outcomes, such as severe side effects and drug resistance. With the accelerated modernization of traditional Chinese medicine (TCM), an increasing body of evidence has shown that several TCM components have significant anticancer activities. Astragaloside IV (AS-IV) is considered the main active ingredient of the dried root of Astragalus membranaceus. AS-IV exhibits various pharmacological effects, such as anti-inflammatory, hypoglycemic, antifibrotic, and anticancer activities. AS-IV possesses a wide range of activities, such as the modulation of reactive oxygen species-scavenging enzyme activities, participation in cell cycle arrest, induction of apoptosis and autophagy, and suppression of cancer cell proliferation, invasiveness, and metastasis. These effects are involved in the inhibition of different malignant tumors, such as lung, liver, breast, and gastric cancers. This article reviews the bioavailability, anticancer activity, and mechanism of AS-IV and provides suggestions for further research of this TCM.